Relações entre a prática da educação a distância e a estrutura organizacional das universidades: processos de inovação e a tradição - Márcia Lopes Reis (EccoS – Revista Científica)
Considering the education at distance as a teaching-learning modality which process of innovation results in institutionalized practices structuration/ desestructuration at the proper university, this article has as objective to consider that the education at distance is taken as a study¿s issue - in the direction of its understanding in deep - with sights of overcoming the resistances that elapse, sometimes, from the scarcity of knowledge about the subject. For that, this article uses metanalisis as metodological passage for understanding that the organizational structure of the university understood here, in general lines, at the aspects of formalization, centralization and complexity of their own peculiarities demand a reorganization when considered distance´s education modality.